Bullying in Irish Education - Stevens, Paul; Stevens, Paul; O'Moore, Mona; O'Moore, Mona (Book collections on Project MUSE., 2013)
This book will be the first definitive review of bullying in Irish education written by researchers and practitioners working in the field. The appeal of this book is twofold. First, it explores bullying from different perspectives within education, specifically pupils, teachers and principals. Second, in addition to it being research based, it also explores the concerns, shortcomings and challenges which bullying presents in the educational environment and proposes realistic strategies and support strategies. Given the keen interest in bullying internationally, this book provides a comparative text sharing research and practice in Ireland.